2020
DOI: 10.7150/thno.46903
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutaredoxin 5 predisposes Cisplatin-resistant Head and Neck Cancer Cells to Ferroptosis

Abstract: Rationale: Loss of iron-sulfur cluster function predisposes cancer cells to ferroptosis by upregulating iron-starvation response, but the role of glutaredoxin 5 (GLRX5) silencing in ferroptosis remains unknown. We examined the role of GLRX5 functional loss in promoting ferroptosis in cisplatin-resistant head and neck cancer (HNC) cells. Methods: The effects of sulfasalazine treatment and GLRX5 gene silencing were tested on HNC cell lines and mouse tumor xenograft models. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 35 publications
(44 reference statements)
1
65
0
Order By: Relevance
“…In human non-hematopoietic cells with GLRX5 deficiency, the reported consequences include a deficit of mitochondrial ISC biogenesis, increased IRP1-mediated repression of ferritin mRNA translation, and elevated TFR1-mediated iron import with subsequent accumulation of cytosolic/mitochondrial iron [63]. It was also observed that cells with GLRX5 deficiency show abnormally high LIP, repressed ferritin levels, and an augmented vulnerability to ferroptosis [169], as appears to be the case also for Pink1 -/-cells. Notions that the mitochondrial dysfunction inherent in PD leads to progressively conspicuous efforts to maximize ISC-biogenesis are also supported by a report that the abundance of the ISC export factor ABCB7 increased abnormally over time in the neurotoxic MPTP mouse model of PD [170].…”
Section: Discussionmentioning
confidence: 80%
“…In human non-hematopoietic cells with GLRX5 deficiency, the reported consequences include a deficit of mitochondrial ISC biogenesis, increased IRP1-mediated repression of ferritin mRNA translation, and elevated TFR1-mediated iron import with subsequent accumulation of cytosolic/mitochondrial iron [63]. It was also observed that cells with GLRX5 deficiency show abnormally high LIP, repressed ferritin levels, and an augmented vulnerability to ferroptosis [169], as appears to be the case also for Pink1 -/-cells. Notions that the mitochondrial dysfunction inherent in PD leads to progressively conspicuous efforts to maximize ISC-biogenesis are also supported by a report that the abundance of the ISC export factor ABCB7 increased abnormally over time in the neurotoxic MPTP mouse model of PD [170].…”
Section: Discussionmentioning
confidence: 80%
“…Targeting biochemical alterations uniquely exhibited by cancer cells may provide therapeutic activity and selectivity in treating cancers 1 . Reactive oxygen species (ROS) are normal by-products of cellular processes, such as mitochondrial metabolism and protein folding.…”
Section: Introductionmentioning
confidence: 99%
“…When the intracellular lipid ROS level exceeds the antioxidant activity of GPX4, it leads to the disruption of redox homeostasis 10 . Ferrous iron can trigger harmful peroxidation of PUFAs in membrane phospholipids by forming toxic lipid radicals, eventually leading to cell death 11 . Iron accumulating within several organs during aging, such as brain and muscle, leads to increased oxidative damage and functional decline.…”
Section: Introductionmentioning
confidence: 99%